The Power of Storytelling: Enhancing English Proficiency through Narrative Practices - Siti Aisyah (Yayasan Insan Cipta Medan, 2025)
This study explores the use of storytelling as a pedagogical tool to enhance English proficiency among intermediate-level language learners at STIT Al-Ittihadiyah Labuhanbatu Utara. Employing a qualitative classroom-based action research design, the intervention integrated a variety of storytelling activities over ten weeks, including oral narratives, peer storytelling, and digital storytelling projects. Data were collected through pre- and post-tests, classroom observations, reflective journals, and semi-structured interviews. The findings reveal significant improvements in students’ vocabulary development, grammatical accuracy, fluency, and narrative coherence. In addition to linguistic gains, students demonstrated increased motivation, confidence, and engagement with the learning process. The study concludes that storytelling not only supports the linguistic aspects of English learning but also fosters a dynamic, interactive, and emotionally resonant classroom environment. It recommends the strategic integration of storytelling practices, including digital storytelling, into English language instruction to promote more holistic language development.